Extensive pelvic hydatid disease mimicking ovarian malignant tumour - Sarkar, Rema Nair; Vani, I.; Lakshmi, A. Bhagya; Radha, T. (International Journal of Research in Medical Sciences, 2017)
Hydatid disease is one of the commonest parasitic infections of the liver, endemic in many countries. Rupture into the peritoneal cavity leading to secondary echinococcosis is a difficult problem to manage. A case of 37 year old female patient presenting with disseminated intra-abdominal hydatid disease mimicking malignant multilocular cystic tumor of the ovary involving the mesentery of the small intestine, omentum and spleen is presented along with a brief review of literature.